Perception of Prolanis Participants About Chronic Disease Management Program Activities (PROLANIS) in the Primary Health Service Universitas Padjadjaran - Risman Ariana; Citra Windani Mambang Sari; Titis Kurniawan (Faculty of Nursing, Universitas Jember, 2019)
Prolanis is a program that the purpose is to handle health problems in Indonesia. However, the participation of prolanis participants in the activities and the presents itself are still low in every month. The purpose of this study was to identify the participants about project activities in UPT Layanan Kesehatan Unpad encompasses perception, seriousness, benefits, obstacles to action and confidence. This quantitative descriptive study was conducted on 81 respondents by means of total sampling. The research data was taken using questionnaire which consisted of 46 statements developed from literature related to prolanis and previously had tested the validity with value range 0,453-0,760 and reliability with result 0,729, then data analyzed descriptively. The results showed that most prolanis participants (54.3%) had good activities with pro-public activities. In addition, there were mostly participants and no response to the disease if there were no prolanis program (50.6%), impact of prolanis (54.3%), current sensitivity of prolanis (53.1%) and belief to follow prolanis (54.3%). While almost all participants (81.5%) had information and instructions to follow prolanis. This action demonstrates good activities but there are still significant obstacles in the framework of existing projects to support existing services for UPT Layanan Kesehatan Unpad with roles to increase participation of prolanis participants.